Ligustri Lucidi Fructus, a traditional Chinese Medicine: Comprehensive review of botany, traditional uses, chemical composition, pharmacology, and toxicity. (30th January 2023) - Cao, Mayijie; Wu, Jie; Peng, Ying; Dong, Baohua; Jiang, Yunxiu; Hu, Changjiang; Yu, Lingying; Chen, Zhimin
Abstract: Ethnopharmacological relevance: Ligustri Lucidi Fructus (LLF) is one of the usual Chinese herbs that has long been used with high therapeutic and condition value. LLF is used for the treatment of dizziness and tinnitus, soreness and weakness of the waist and knees, premature greying of the hair, the darkness of the eyes, internal heat and thirst, bone steam and hot flashes and other symptoms. Aim of the study: This review reviews botany, traditional uses, processing, phytochemistry, quality control, pharmacology, toxicity and pharmacokinetics to better understand its therapeutic potential. Materials and methods: The literature on LLF was obtained from Google Scholar and Baidu Scholar, PubMed, ScienceDirect, SciFinder, Web of Science, China National Knowledge Infrastructure (CNKI), WAN FANG DATA and libraries. Some local books, official websites, PhD or MS's dissertations were also included. Phytochemical constituents' structures were drawn by ChemDraw software. Results: So far, Multiple chemical components were isolated and identified from LLF, mainly including terpenoids and flavonoids. Modern studies have shown that LLF extracts and compounds have a wide range of pharmacological effects, including antitumor, liver protection, blood glucose, lipid-lowering, immune regulation, and other aspects. Conclusions: LLF occupies an important position in the traditional medical system. It is cost-effective and is a significant plant with therapeutic applications in modern medicine. However, further in-depth studies are needed to determine the medical use of this plant and its chemical composition, pharmacological activity, quality control, toxicity and pharmacokinetics. Graphical abstract: Ligustri Lucidi Fructus (LLF) is one of the usual Chinese herbs that has been used for thousands of years with high therapeutic and condition value. This review reviews botany, traditional use, processing, phytochemistry, quality control, pharmacology, and toxicity to better understand its therapeutic potential.Multiple chemical components were isolated and identified from LLF, mainly including terpenoids and flavonoids. Modern studies have shown that LLF extracts and compounds have a wide range of pharmacological effects, including antitumor, liver protection, blood glucose, lipid-lowering, immune regulation, and other aspects.女贞子（Ligustri Lucidi Fructus）是一种常见的中药，已经使用了数千年，具有很高的治疗和调理价值。本综述对植物学、传统用途、加工、植物化学、质量控制、药理学和毒性进行了综述 ， 以更好地了解其治疗潜力。从女贞子中分离和鉴定了多种化学成分，主要包括萜类和黄酮类。现代研究表明，女贞子提取物和化合物具有广泛的药理作用，包括抗肿瘤、保肝、降血糖、降血脂、免疫调节以及对其他方面的影响. Image 1 Highlights: A review of botany, traditional usage, phytochemical, quality control, pharmacology and toxicity of Ligustri Lucidi Fructus. This thesis draws on the latest research literature on Ligustri Lucidi Fructus up to 2022. Mapping of the structures of 122 chemical components found in Ligustri Lucidi Fructus. Confirms that Ligustri Lucidi Fructus has no significant toxic side effects. The future development direction of Ligustri Lucidi Fructus is introduced.